The Effect of Infusing Soursop Leaves (Annona muricata L.) on Vaginal Discharge in Women of Childbearing Age: A Randomized Clinical Trial at the Lolo Community Health Center, Kerinci Regency, Jambi, Indonesia - Yohana Suganda; Gusmadewi; Rahmatul Ulya; Mekar Zenni Radhia (Sriwijaya Journal of Obstetrics and Gynecology, 2025)
Introduction: Vaginal discharge (leukorrhea) is a common gynecological complaint among women of childbearing age. While physiological discharge is normal, pathological discharge can be indicative of underlying infections or conditions. This study aimed to investigate the efficacy of soursop leaf infusion (Annona muricata L.) as a complementary treatment for vaginal discharge in women of childbearing age. Methods: A randomized controlled trial was conducted at the Lolo Community Health Center, Kerinci Regency, Jambi, Indonesia. Women aged 15-49 years presenting with vaginal discharge were randomly assigned to either the intervention group (soursop leaf infusion) or the control group (standard care). The intervention group received soursop leaf infusion twice daily for seven days, while the control group received standard care as per the health center's protocol. The primary outcome was the reduction in vaginal discharge symptoms (amount, color, odor, and associated discomfort) after seven days. Secondary outcomes included changes in vaginal pH and microbiological assessment. Results: A total of 130 women participated in the study (65 in each group). After seven days, the intervention group showed a significantly greater reduction in vaginal discharge symptoms compared to the control group (p < 0.05). The amount, color, and odor of discharge improved significantly in the intervention group, along with a reduction in associated discomfort such as itching and irritation. Vaginal pH was also normalized in the intervention group, and microbiological assessment revealed a decrease in pathogenic microorganisms. Conclusion: Soursop leaf infusion (Annona muricata L) appears to be a safe and effective complementary treatment for vaginal discharge in women of childbearing age. Its antimicrobial and anti-inflammatory properties may contribute to its beneficial effects. Further research is warranted to explore its long-term efficacy and potential use in combination with conventional therapies.